(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of this study is to assess critically the influence of advertisement on households Youth, find out the challenges in usage of Print Electronic Media. Also we focused on the impact of FM as a Media, Media is More Effective FM or Print. We can likewise consider from the outcomes that specialist’s prescription for medication is responsive to exposure. Therefore, internet and TV are used more by consumers followed by newspapers. Radio and magazines are less used by consumers. Independent variables such as gender, age and annual family income affect newspaper and internet on the parameter of time spent per media, whereas it does not affect TV, radio and magazines on time spent. So gender, age and family income needs to be considered by adverting agencies while going for newspaper and internet ads.